Human Reliability Analysis on Fresh Fruit Bunches Sorting Workers - Agustina Hotma Uli Tumanggor; Chynthia Eka Fayuning Tjomiadi; Madschen Sia Mei Ol Siska Selvija Tambun (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Demand for Crude Palm Oil (CPO) at PT. Wijaya Borneo Tiganna for this year has increased. However, the increase in production was not in line with human error of 74% in the Fresh Fruit Bunches (FFB) Sorting Department from the 80% minimum percentage desired by the company. The purpose of this study was to analyze the reliability value of sorting workers. The method used is the Human Reliability Assessment Method seen from related tasks and context related to identify Human Error Probability (HEP) with a fault tree to provide recommendations for reducing human error. There are 3 types of rework in the TBS Sorting Section. The HEP using the HEART method is 1.1103148 while the CREAM method is 0.10608. The reliability of workers in carrying out tasks can still be improved with skills and accuracy in the sorting and grading of FFB.